Secrets of Success in a Landscape of Fear: Urban Wild Boar Adjust Risk Perception and Tolerate Disturbance - Stillfried, Milena; Gras, Pierre; Börner, Konstantin; Göritz, Frank; Painer, Johanna; Röllig, Kathleen; Wenzler, Moritz; Hofer, Heribert; Ortmann, Sylvia; Kramer-Schadt, Stephanie (Frontiers in Ecology and Evolution, 2017)
In urban areas with a high level of human disturbance, wildlife has to adjust its behavior to deal with the so called “landscape of fear.” This can be studied in risk perception during movement in relation to specific habitat types, whereby individuals trade-off between foraging and disturbance. Due to its high behavioral plasticity and increasing occurrence in urban environments, wild boar (Sus scrofa) is an excellent model organism to study adjustment to urbanization. With the help of GPS tracking, space use of 11 wild boar from Berlin's metropolitan region was analyzed: we aimed at understanding how animals adjust space use to deal with the landscape of fear in urban areas compared to rural areas. We compared use vs. availability with help of generalized linear mixed models. First, we studied landscape types selected by rural vs. urban wild boar, second, we analyzed distances of wild boar locations to each of the landscape types. Finally, we mapped the resulting habitat selection probability to predict hotspots of human-wildlife conflicts. A higher tolerance to disturbance in urban wild boar was shown by a one third shorter flight distance and by an increased re-use of areas close to the trap. Urban wild boar had a strong preference for natural landscapes such as swamp areas, green areas and deciduous forests, and areas with high primary productivity, as indicated by high NDVI (normalized difference vegetation index) values. The areas selected by urban wild boar were often located closely to roads and houses. The spatial distribution maps show that a large area of Berlin would be suitable for urban wild boar but not their rural conspecifics, with the most likely reason being a different perception of anthropogenic disturbance. Wild boar therefore showed considerable behavioral plasticity suitable to adjust to human-dominated environments in a potentially evolutionarily adaptive manner.